Application of Big Data Mining Technology in Blockchain Computing - Zejian Dong (International Journal of Informatics and Information Systems, 2023)
Big data in the modern science and technology and social activities play an important role, on the one hand, a large number of new applications and technology into our lives, in the use of these new technologies to produce a large amount of data, on the other hand, big data as one of the most important digital assets, many of the development of new technologies also rely on large data as support. This paper focuses on the research and application of big data mining technology in blockchain computing. Firstly, this paper extracts the corresponding transaction data according to the Bitcoin address and constructs the transaction features to get the Bitcoin data set. Then, the data features are processed. Then, three algorithm models, SVM, Adaboost and Random Forest, are selected to model and analyze the preprocessed data combined with different sampling strategies. According to the comprehensive performance of the model and its shortcomings, the model is selected and improved.